2006
DOI: 10.1269/jrr.47.61
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Triphlorethol-A from Ecklonia cava against Ionizing Radiation in vitro

Abstract: We studied the cytoprotective effect of triphlorethol-A against gamma-ray radiation-induced oxidative stress. In this study, hydrogen peroxide, which is a reactive oxygen species (ROS), was detected using 2',7'-dichlorodihydrofluorescein diacetate (DCF-DA) assay. Triphlorethol-A reduced intracellular hydrogen peroxide generated by gamma-ray radiation. This compound provided protection against radiation-induced membrane lipid peroxidation and cellular DNA damage which are the main targets of radiation-induced d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 17 publications
0
30
0
Order By: Relevance
“…In addition, triphlorethol-A protected against cellular damage from ionizing radiation via inhibition of apoptosis (Kang et al 2006). Triphlorethol-A induced the antioxidant enzyme heme oxygenase-1 via activation of the NF-E2-related factor 2 transcription factor ).…”
Section: Triphlorethol-a Improves Impaired Dna Repair Capacity 813mentioning
confidence: 98%
“…In addition, triphlorethol-A protected against cellular damage from ionizing radiation via inhibition of apoptosis (Kang et al 2006). Triphlorethol-A induced the antioxidant enzyme heme oxygenase-1 via activation of the NF-E2-related factor 2 transcription factor ).…”
Section: Triphlorethol-a Improves Impaired Dna Repair Capacity 813mentioning
confidence: 98%
“…Thus, the elimination of the free radical species can act as a target in the search for radioprotective compounds. To date, several natural products have been shown to protect cells against radiation-induced damage by virtue of their antioxidant properties (Kang et al 2006). The present study showed that geraniin, a tannin isolated from N. tetragona Georgi var., effectively protected cells against radiation-induced damage via a mechanism involving the regulation of cellular antioxidant enzyme activity, by inhibition of oxidative stress and free radical scavenging.…”
Section: Discussionmentioning
confidence: 49%
“…Cells were exposed to γ-ray from a 60 Co γ-ray source (MDS Nordion C-188 standard source, Jeju National University, Jeju, Korea) at a dose rate of 1.5 Gy/min (Kang et al 2006). …”
Section: γ-Radiationmentioning
confidence: 99%
See 1 more Smart Citation
“…This mainly occurs in biomembranes, where the content of unsaturated fatty acids is relatively high. This leads to the destruction of cellular membranes, and is related to the development of many chronic diseases such as aging and cancer [2][3]. Other studies have measured several markers of lipid peroxidation in the human body such as the thiobarbituric acid reactive substances (TBARS), ethylene (ethene) and pentane in the breath gas, lipid hydroperoxides, and aldehydes such as malonaldehyde (MDA) [4].…”
Section: Introductionmentioning
confidence: 99%